PSYCHOLOGY IN DEVELOPING COUNTRIES: PEOPLE-CENTRED DEVELOPMENT AND LOCAL KNOWLEDGE - Van Vlaenderen, Hilde (PINS-Psychology in Society, 2026)
In developing countries, psychology is faced with the challenge of providing knowledge and services that contribute to national development. However, opinions on how psychology can play a role in processes of rapid social change vary between psychologists of different persuasions. A short overview is presented of the various possible roles of psychology, congruent with different development paradigms. Adoption of a people centred development paradigm, which is based on people’s participation and empowerment and which relies on people’s local knowledge is proposed. Subsequently the Participatory Action Research approach is introduced as a social science paradigm congruent with a people centred approach. The main characteristics of the approach are discussed and examples are provided of Participatory Action Research in practice.